2014
DOI: 10.1177/1479972313516878
|View full text |Cite
|
Sign up to set email alerts
|

Coping and social problem solving correlates of asthma control and quality of life

Abstract: In a sample of adults with asthma receiving care and medication in an outpatient pulmonary clinic, this study tested for statistical associations between social problem-solving styles, asthma control, and asthma-related quality of life. These variables were measured cross sectionally as a first step toward more systematic application of social problem-solving frameworks in asthma self-management training. Recruitment occurred during pulmonology clinic service hours. Forty-four adults with physician-confirmed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Depending on the culture, gender can affect health status and health outcomes by increasing exposure to health risk factors, and by limiting access to health care and to health information. 34 In KSA the proportion of female patients with uncontrolled asthma is almost 1.5 times greater compared with that of among male patients, 8 and studies in Turkey, 27 Italy, 35 and in the US, 12 show that females have poorer asthma control than males. Our results are consistent with these findings as we found that females had approximately 2 times greater odds of having uncontrolled asthma (OR=2.0; 95% CI=1.0-4.0) compared with males.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the culture, gender can affect health status and health outcomes by increasing exposure to health risk factors, and by limiting access to health care and to health information. 34 In KSA the proportion of female patients with uncontrolled asthma is almost 1.5 times greater compared with that of among male patients, 8 and studies in Turkey, 27 Italy, 35 and in the US, 12 show that females have poorer asthma control than males. Our results are consistent with these findings as we found that females had approximately 2 times greater odds of having uncontrolled asthma (OR=2.0; 95% CI=1.0-4.0) compared with males.…”
Section: Discussionmentioning
confidence: 99%
“…22 Problem solving is also related to depression and HRQOL in both population with a disease and healthy population. 23,24 Whether coping strategy, problem-solving skills, and depression are independently related to HRQOL in patients receiving outpatient rehabilitation treatment is unknown. The present study investigated these relations in patients participating in an outpatient stroke rehabilitation program.…”
mentioning
confidence: 99%
“…This is clinically relevant as different treatments or interventions may be applied to this difficult to control group. There is evidence that adjunct socio-behavioral interventions to traditional asthma management improve outcomes [35]; however, these interventions are perceived as time and labor intensive. By identifying a risk factor profile that includes measures of racial/ethnic discriminatory experiences and inflammatory biomarkers, we may be better able to screen and identify individuals who are most susceptible to this type of psychosocial stress, and thus, more likely to benefit from such therapy.…”
Section: Discussionmentioning
confidence: 99%